What is service design? - Lawrence, Adam; Stickdorn, Marc; Hormess, Markus; Schneider, Jakob (Economist) (O'Reilly Media, 2019)
Companies and their customers today often don't focus on the same things. While a restaurant may work hard to create an exciting new menu item, diners care more about courtesy. A bank will spend thousands promoting trust while customers struggle to access their website. This report explains how service design can help your organization innovate to deliver great experiences, not just great products, by understanding your customers' needs. Service design experts Adam Lawrence, Marc Stickdorn, Markus Hormeß, and Jakob Schneider explain that service design is a mindset, a process, a toolset, and a cross-disciplinary language. You'll learn how cross-functional teams can create and orchestrate great customer or employee experiences that satisfy the requirements of the business, the user, and other stakeholders. This report explores how: Service design applies to physical and digital products as well as services Today's informed customers have created a new challenge for businesses Service design is similar to design thinking and compatible with Agile and Lean Designers can promote low-risk progress through iterative prototyping Lightweight, iterative research can keep teams from solving the wrong problem This approach offers a common language for cross-silo collaboration.